Investment Climate and Investment Attractiveness of Macroregions of Russia - M. Yu. Elsukov; A. V. Mayevsky; E. F. Cheberko (Управленческое консультирование)
In accordance with the requirements of the law on strategic planning, macro-regions of the Russian Federation have been identified. The next solution is to develop strategies for the socio-economic development of macro-regions. Social and economic development requires financial resources. In a market economy, providing resources involves attracting investment. The distribution of investment between regions is uneven. Indicators of investments in fixed assets, financial investments of organizations and foreign direct investment indicate the attractiveness for investors of a limited number of regions. Assessments of investment attractiveness and investment climate are of interest to authorities, investors and local business communities. Guided by various interests and using original techniques, ratings of investment attractiveness and the investment climate of the regions are formed in scientific research and consulting developments. The results of these works are very contradictory. The article is devoted to the definition of regions — centers of investment activity in the macroregions of the Russian Federation, comparison of ratings agencies on the state of the investment climate and investment attractiveness of the regions.